1998
DOI: 10.1097/00000658-199805000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns in the Management of Splenic Trauma

Abstract: Nonoperative management of blunt splenic injuries has replaced splenorrhaphy as the most common method of splenic conservation. The criteria have been extended to include patients previously excluded from this form of therapy. As a result, 65% of all blunt splenic injuries and select stab wounds can be managed with minimal transfusions, morbidity, or mortality, with a success rate of 98%. Splenectomy, when necessary, continues to be associated with excessive transfusion and an inordinately high postoperative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
193
1
14

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(219 citation statements)
references
References 28 publications
7
193
1
14
Order By: Relevance
“…NOM failure increased length of hospital stay and increased mortality in selected subsets of patients (9,32). Accordingly, NOM has shorter length of hospital stay than operative management in patients with isolated solid organ injuries (30).…”
Section: Discussionmentioning
confidence: 99%
“…NOM failure increased length of hospital stay and increased mortality in selected subsets of patients (9,32). Accordingly, NOM has shorter length of hospital stay than operative management in patients with isolated solid organ injuries (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although catastrophic injury is uncommon, it is possible many asymptomatic injuries to the spleen go undetected. Hemodynamically stable patients with splenic injuries after blunt trauma are successfully treated nonoperatively in greater than 70% of cases [5].…”
Section: Discussionmentioning
confidence: 99%
“…Classic criteria for nonoperative management include haemodynamic stability, absence of other clear cut indications for laparotomy or associated injuries requiring surgical intervention, absence of health conditions that carry increased risk of bleeding, grade I-III injuries and patients under 55 years of age. 15 Myers et al reported successful management of solid visceral injuries irrespective of grades, in haemodynamically stable patients of age more than 55 years. 96 So the choice between operative and nonoperative treatment should be guided primarily by haemodynamic considerations rather than grades or severity of organ injury.…”
Section: Managementmentioning
confidence: 99%